Industrial training report: Majlis Agama Islam dan ‘Adat Melayu Perak / Mohamad Aidil Afiq Mohamad Akmal - Mohamad Akmal, Mohamad Aidil Afiq (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Industry training is a mandatory subject for all diploma students in Diploma In Information Management (IM110). This industrial training consists of two months from 22th July untill 13 Septembers 2024. The students were given a choice which company or organisation they want to undertake for industrial training. As part of the process, the students will need to submit the required doucuments to the lecturer for evaluation before being sent to the selected organization for the application. After the application is successfully approved by the organisation and lectures, the students will proceed with the process by undergoing industrial training at the organisation. After that, I have been accepted from the company that I applied for my industrial training at Majlis Agama Islam Dan ‘Adat Melayu Perak Ipoh, Perak. Additionally, I want to share the experiences that was important, valuable and enjoyable during my two months training at Majlis Agama Islam Dan ‘Adat Melayu Perak Ipoh, Perak. Furthermore, this report required myself to prepared all of the activities and programs that I participated while I’m in the organization.